The multidimensional landscape of pharmacovigilance: development and management - Hagemann, Ulrich (Henry Stewart Talks, 2023)
Pharmacovigilance, Production of medicinal products, Epidemiology and statistics, Understanding ‘risk’ and ‘benefit’, Measuring risk, Law and legislation, Management of pharmacovigilance, Stakeholders and partners, Media and patient communication